1971
DOI: 10.1017/s0021859600064479
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the utilization of the energy of food in laying hens

Abstract: SUMMARYThe efficiency of utilization of the energy of food in White Leghorn laying hens for egg production was measured. A ration with a gross energy of 4469 kcal/kg dry matter and 19·4% crude protein had a metabolizable energy of 80·1±1·7% of the gross energy, and 78·5±5·3% of the metabolizable energy was present as net energy.The maintenance requirement of metabolizable energy of White Leghorn hens weighing 1·723±48·5 kg and a production of 19·3±0–49 eggs per month was 125·8 kcal/kg0·75/24 hr.The energy cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

1973
1973
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 2 publications
2
3
0
1
Order By: Relevance
“…compares with values of 507 to 560 kj ME/Wkg 0>75 reported by Waring and Brown (1967), Burlacu andBaltac (1971), O'Neill andJackson (1974) and Farrell (1975), and 415 kj ME/W°-75 (Grimbergen, 1970) for White Leghorn hens adjusted to the same temperature.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…compares with values of 507 to 560 kj ME/Wkg 0>75 reported by Waring and Brown (1967), Burlacu andBaltac (1971), O'Neill andJackson (1974) and Farrell (1975), and 415 kj ME/W°-75 (Grimbergen, 1970) for White Leghorn hens adjusted to the same temperature.…”
supporting
confidence: 72%
“…The regression of energy balance on ME intake in studies reported by Waring and Brown (1967), Burlacu and Baltac (1971) and Farrell (1975) yielded values of 79% to 86% for the efficiency of utilization of ME for maintenance and production of White Leghorn hens. In all cases linear regression was appropriate, indicating similar efficiencies above and below maintenance.…”
Section: Comparison With Calorimetric Datamentioning
confidence: 88%
See 2 more Smart Citations
“…As exigências energéticas para produção de ovos variam de 1,92 (Sakomura, 1989) a 3,15 (Combs, 1968) e as eficiências, de 61,0% a 83,7% (Santomá, 1991). Sakomura et al (1993a), ao elaborarem equação de predição das exigências energéticas para poedeiras leves, consideraram eficiência de conversão da energia da dieta para produção de ovos de 80%, que foi estabelecida de acordo com o proposto por Waring & Brown (1965), Grimbergen (1970), Burlacu & Baltac (1971) e NRC (1984. Porém, os resultados deste experimento (62%), assim como os descritos por Coon & Zhang (1999), de 63%, podem indicar que a eficiência energética sugerida pelos trabalhos pioneiros pode estar superestimada, ocasionando subestimativa das exigências energéticas para produção de ovos.…”
Section: Resultsunclassified